Penanaman Nilai Toleransi dan Kebhinekaan melalui Kisah Dakwah Rasulullah di Madinah dalam Pembelajaran SKI di Madrasah Ibtidaiyah - Ainnaya Faatihah; Devi Rahma Islami; Alma Maroha Faisi; Fiantika Yuni Rosayanti; Fatkhatun Nikmah; Munaeroh; Mei Zahra Habibah Qhalbi; Dian Rif’yati (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Instilling values of tolerance and diversity from an early age is an important aspect in shaping the character of students to have noble morals and be able to live harmoniously amid diversity. This study aims to examine the principles of tolerance and diversity through the story of the Prophet's preaching in Medina in SKI learning at the MI level. The research method used is qualitative by accessing data through library research. The data collection process in this study was carried out by reading and analyzing books and scientific articles. The results of the study show that the story of the Prophet's preaching in Medina, contextualized with the daily lives of students, can be an effective learning medium for conveying the values of togetherness, mutual respect, and acceptance of differences. Teachers have an important role in facilitating reflective discussions that aim to relate the meaning of the story to the context of students' daily lives. This implementation has a positive impact on students' attitudes, making them more open and appreciative of differences in social interactions at school. By instilling tolerance from an early age, it is hoped that social conflicts can be prevented, the ability to adapt to new environments can be improved, and emotional intelligence can be developed so that children appreciate differences.